PENGARUH LIKUIDITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MELALUI ROA - Supami, Supami (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2018)
The purpose of this study was to determine the effect of liquidity and firm growth on firm value with ROA as intervening variable. The method in this research is a kind of causal comparative research with quantitative approach. Analytical technique of this research using path analysis technique. The result of research that liquidity influence to company value, company growth influence to company value, liquidity influence to Return On Assets, company growth influence to Return On Assets, Return On Assets influence to company value. The conclusions of liquidity affect the value of the company through the Return On Assets, corporate growth affect the value of the company through the Return On Assets. For further research use ROA as moderation.